Geochronology, geochemistry, and Hf isotopes of mafic rocks from Dalabute ophiolitic mélange in West Junggar, Xinjiang (NW China): Implications for the magmatic source and tectonic setting. (11th February 2020) - Li, Hai; Li, Yongjun; Yang, Gaoxue; Wang, Zuopeng; Ren, Pengfei; Chang, Haoying
Abstract : Several Palaeozoic ophiolitic mélanges distributed in the West Junggar, Xinjiang, are remnants of the Paleo‐Asian Ocean evolution. They are important keys for studying the component, tectonic evolution, and crust–mantle interaction of the Central Asian Orogenic Belt (CAOB). This paper presents petrology, zircon U‐Pb chronology, geochemistry, and Hf isotope data of mafic rocks from the Dalabute ophiolitic mélange, West Junggar. The zircon U‐Pb chronology data of gabbro in the Dalabute ophiolitic mélange can be divided into two groups. The first group magmatic zircons yield a weighted mean age of 389.7 ± 7.7 Ma. It suggests that gabbros of the Dalabute ophiolitic mélange were formed during the period of Early‐middle Devonian, which represents the main period that the Dalabute back‐arc ocean basin expanded. The second group inherited zircons with ages ranging from 910 to 975 Ma were interpreted as Neoproterozoic materials of basement entered its magmatic source. Geochemical characteristics show that the mafic rocks from the Dalabute ophiolitic mélange can be subdivided into alkaline and tholeiite series. Whole‐rock and Hf isotopic data indicate that alkaline basalts have the signatures of typical OIB and formed in the oceanic island or seamount settings related to mantle plume, which were most likely derived from an enriched mantle source. Besides, tholeiitic rocks exhibit the features of MORB and generated in an immature back‐arc basin in the supra‐subduction zone. Their magmas originated from a depleted mantle that had been metasomatized by subduction‐related fluids and contaminated by materials with crustal nature. Therefore, Dalabute ophiolites are supposed to be generated from a back‐arc oceanic basin, which is relate to intra‐subduction and with mantle plumes developed within it. These results jointly provide convincing evidence for the evolution and property of the Dalabute ophiolite in the West Junggar and further supply reference and base for reconstruct the evolutionary history of the CAOB.